2008
DOI: 10.1088/0957-4484/19/8/085602
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of mercaptothiadiazole-functionalized gold nanoparticles and their self-assembly on Au substrates

Abstract: Gold nanoparticles (AuNPs) stabilized with mercaptothiadiazole ligands, 2,5-dimercapto-1,3,4-thiadiazole (DMT), 5-amino-2-mercapto-1,3,4-thiadiazole (AMT) and 5-methyl-2-mercapto-1,3,4-thiadiazole (MMT), were prepared by the reaction of the respective ligands with HAuCl(4) and NaBH(4) in an aqueous medium. TEM images show that the average size of AuNPs was 6.5 ± 0.5 nm, irrespective of the capping ligands. The colloidal solution of both DMT-capped AuNPs (DMT-AuNPs) and AMT-capped AuNPs (AMT-AuNPs) were highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 108 publications
5
55
0
Order By: Relevance
“…These observations suggested that the (111) plane was the predominant orientation of as-prepared GNPs. 30 The selected areas electron diffraction patterns of the GNPs (Figure 2B), corresponding to the face-centered cubic crystalline structure, further corroborated the results of XRD measurement.…”
Section: Characterization Of As-prepared Gnpssupporting
confidence: 77%
“…These observations suggested that the (111) plane was the predominant orientation of as-prepared GNPs. 30 The selected areas electron diffraction patterns of the GNPs (Figure 2B), corresponding to the face-centered cubic crystalline structure, further corroborated the results of XRD measurement.…”
Section: Characterization Of As-prepared Gnpssupporting
confidence: 77%
“…A single peak observed at 1600.43 cm -1 corresponds to amide linkage and bending vibration of N-H groups of proteins, respectively where as in case of AgNPs spectra, the peaks observed at 1750, and 1631 cm -1 , represents the C=O stretch, -C=C stretch of esters and amide group respectively, which corresponds to heterocyclic compounds like proteins. This serves as support for proteins present in the supernatant extract as capping agents for the biosynthesized AgNPs [12,13]. It has been reported that proteins may bind to the nanoparticles either with the free amine groups or cysteine residues and cap the nanoparticles [8].…”
Section: Ft-ir Investigations Of Silver Nanoparticlesmentioning
confidence: 99%
“…The IR bands at *1709.83 and 1369 cm -1 are characteristic of C-O and C-O stretching modes, respectively, of the carboxylic group (Kathiraven et al 2015). The strong band at *1037 cm -1 arises from C-O-C and C-OH vibrations (Solomun et al 2004;Ankamwar et al 2005;Huang et al 2007;Kannan and Abraham John 2008). Earlier studies revealed that the absorbance bands at *1109 and 1726 cm -1 in curve were associated with the stretch vibration of -C-O and -C=C respectively (Zhu 2000).…”
Section: Characterization Of Silver Nanoparticlesmentioning
confidence: 99%